2022
DOI: 10.1002/csr.2289
|View full text |Cite
|
Sign up to set email alerts
|

Theconcave–convexeffects of environmental, social and governance onhigh‐techfirm value: Quantile regression approach

Abstract: This study aims to investigate the nonlinear relationship between environmental, social and governance (ESG) and firm value (FV). The sample includes 38 Taiwan Stock Exchange listed high-tech firms with ESG disclosure between 2005 and 2020.Quantile regression estimation results indicate there is a nonlinear concave-convex ESG-FV relationship, which is also verified by the U-test. Furthermore, there is a different relationship between the individual ESG pillars and FV. The nexus between the environmental and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…Second, the results confirm that the ESGE-CFP relationship also has an inverted U-shaped pattern, which is justified by the law of diminishing marginal returns (LDMR). This finding supports the TMGT perspective and agrees with the contentions of Lahouel et al (2022), and Wu and Chang (2022). The optimal ESGE value is 43.049 (Table 3; Figure 4B) and is higher than the average ESGE value (32.747), which suggests that most TSE listed firms are in the ESG-low regime.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Second, the results confirm that the ESGE-CFP relationship also has an inverted U-shaped pattern, which is justified by the law of diminishing marginal returns (LDMR). This finding supports the TMGT perspective and agrees with the contentions of Lahouel et al (2022), and Wu and Chang (2022). The optimal ESGE value is 43.049 (Table 3; Figure 4B) and is higher than the average ESGE value (32.747), which suggests that most TSE listed firms are in the ESG-low regime.…”
Section: Discussionsupporting
confidence: 86%
“…First, the results confirm an inverted U-shaped ESG-CFP relationship, which infers TSE listed enterprise managers must be conscious of diminishing marginal benefits on increased ESG activity as beyond the threshold point, resources would be more effective if reallocated away from ESG activities. Equally, these findings support the "too-much-of-a-good-thing (TMGT)" perspective (Trumpp & Guenther, 2017), and consistent with the contentions of Azmi et al (2021), Wu and Chang (2022).…”
Section: Discussionsupporting
confidence: 82%
“…This result supports H1. In the existing literature, despite the lack of direct evidence of national ESG performance, researchers have confirmed that, compared with the unified conclusion of fixed effects, the quantile approach shows that ESG performance has a differentiated impact on enterprises with different values (Wu & Chang, 2022; Zhang et al, 2020), sustainable development capabilities (Teng et al, 2021), and scales (Gregory, 2022). Therefore, we believe that panel fixed effects are flawed in characterizing the impact of national ESG performance on green innovation.…”
Section: Resultsmentioning
confidence: 99%
“…Their findings signal a nonlinear relationship between the two. Therefore, a balance between ESG benefits and costs must be maintained by finding a certain level of ESG (Yu et al, 2018;Wu and Chang, 2022). Hence, the nonlinear connectivity also needs to be explored to find how ESG associates with a firm's value to a certain level (Yu et al, 2018;Wu and Chang, 2022).…”
Section: Literature Review Theoretic Agenda and Hypotheses Formulatio...mentioning
confidence: 99%